Increasing net present value in sublevel caving: incorporating discount rate as an essential input for mineable inventory and scheduling - Loewen, S (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Net present value (NPV) is a fundamental metric in project evaluation, providing a basis for comparing the economic strengths of various projects and mine plans. Central to an NPV calculation is the consideration of the time value of money through the application of a discount rate. This paper investigates the integration of the discount rate as a primary parameter within mineable inventory selection and production scheduling. The objective is to optimise the footprint and shut-off strategy to increase discounted operating cash flow (DOC) and hence the NPV of sublevel caving (SLC) mine plans relative to those generated by conventional methods using a static cut-off value. Employing a simplified SLC model, the paper details a mathematical approach for determining a dynamic cut-off value that prevents reduction in DOC due to mining a too-low grade of ore early within the mine schedule. Additionally, this paper presents a computer program created by the author which applies this methodology to generate SLC inventories and production schedules via material flow simulations. Comparative examples are provided to illustrate the impact on mine plans using this methodology and those developed without considering the time value of money.